The demand for high-skilled workers and immigration policy - Thomas K. Bauer; Astrid Kunze (Institute for the Study of Labor (IZA), 2004)
This paper provides a descriptive analysis of the demand for high-skilled workers using a new firm data set, the IZA International Employer Survey 2000. Our results suggest that while workers from EU-countries are mainly complements to domestic high-skilled workers, workers from non-EU countries are hired because of a shortage of high-skilled labour. The paper, furthermore, provides a short description of recent German policy initiatives regarding the temporary immigration of high-skilled labour. In view of our descriptive results these temporary immigration policies seem, however, to satisfy only partly the demand of firms interested in recruiting foreign high-skilled workers. A more comprehensive immigration policy covering also the permanent immigration of high-skilled workers appears to be necessary.
Keywords: J61; F22; 330; migration; high-skilled workers; IZA employer survey; Hochqualifizierte Arbeitskräfte; Arbeitsnachfrage; Einwanderungsrecht; Migrationspolitik; Schätzung; Deutschland